Comprehensive Tuberculosis Management to Improve Self-Management and Physical Health Status: A Systematic Review - Ardiana, Husna; Ardiana, Husna; Priyantini, Diah; Fauziah, Anis (International Journal of Psychosocial Rehabilitation, 2020)
One of the problems in tuberculosis treatment is nonadherence in undergoing treatment, which has an impact on physical health status. Physical health status is affected by physical, psychological, social and spiritual changes. The purpose of this review is to explain interventions that can improve tuberculosis self-management in improving physical health status. Six databases were used including Scopus, CinaHL, ProQuest, ScienceDirect, and Google Scholar using the keywords "tuberculosis", "pulmonary tuberculosis", "self-management", "intervention" and "treatment". Journal searches were limited to 2015-2020 using Bahasa and English. We identified 1387 articles of which 16 were systematically relevant to this review. This study found that efforts to improve self-management and health status of tuberculosis patients were divided into five categories of interventions. The interventions include physical interventions, psychological interventions, social interventions, spiritual interventions and comprehensive management of tuberculosis. The present review shows that, to achieve an increase in physical health status in tuberculosis patients, a comprehensive intervention is needed. The paper emphasizes the need for more research on efforts to improve the physical health status of tuberculosis patients.